Design and implementation of fuzzy logic based modified real-reactive power control of inverter for low voltage ride through enhancement in grid connected solar PV system. (August 2020) - Roselyn, J. Preetha; Chandran, C. Pranav; Nithya, C.; Devaraj, D.; Venkatesan, R.; Gopal, Varun; Madhura, Sai
Abstract: In a grid connected solar PV system, during grid faults, increase in grid current, dip in voltage at point of common coupling and overshoot in dc link voltage in the inverter side are observed. The solar PV system gets disconnected from the grid whenever the grid voltage goes below a certain nominal value in order to safeguard the cascaded power converter systems from high currents and over voltages. This paper proposes an intelligent fuzzy based real and reactive power control of inverter for effective Low Voltage Ride Through (LVRT) capability during grid faults. The proposed fuzzy logic based modified inverter real and reactive power control strategy, stabilizes the grid voltage by injecting reactive current and limits the grid over current by reducing active power flow into the grid. To regulate the overshoot in dc link voltage during grid faults, a braking chopper and dynamic braking resistor strategies are included in the proposed LVRT scheme. The performance of the proposed inverter control strategy is studied through simulation of 100 kW grid connected solar PV system in MATLAB/SIMULINK 2018a platform. The algorithm is validated in real time hardware of 1 kW grid connected solar PV system. The simulation and hardware results validate the superior performance of the proposed inverter LVRT control strategy in comparison with other conventional schemes during grid faults.